2004
DOI: 10.1103/physrevlett.93.205501
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of Micro-eV Energies in Nanocrystalline Microstructures

Abstract: The phonon density of states of nanocrystalline bcc Fe and nanocrystalline fcc Ni 3 Fe were measured by inelastic neutron scattering in two different ranges of energy. As has been reported previously, the nanocrystalline materials showed enhancements in their phonon density of states at energies from 2 to 15 meV, compared to control samples composed of large crystals. The present measurements were extended to energies in the micro-eV range, and showed significant, but smaller, enhancements in the number of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In measurements of phonons in the µeV energy range [279], it was found that the enhancement in the phonon DOS around 10 µeV was only about half of what was found around 10 meV. Some enhancement of the phonon DOS is expected owing Figure 27.…”
Section: Low-energy Vibrations Of Nanostructuresmentioning
confidence: 90%
“…In measurements of phonons in the µeV energy range [279], it was found that the enhancement in the phonon DOS around 10 µeV was only about half of what was found around 10 meV. Some enhancement of the phonon DOS is expected owing Figure 27.…”
Section: Low-energy Vibrations Of Nanostructuresmentioning
confidence: 90%
“…Phonon softening in these structures was attributed to grain boundary atoms and the decrease of the phonon lifetime was attributed to phonon scattering at the grain boundaries 7,8,11,12,15,18,21,23,24 . In some nanocrystalline structures an enhancement of high-energy modes above the cut-off energy was observed which was attributed to surface oxides 12,16 , grain boundary atoms 9,21 or to changes in the inter-atomic force constants 11,18,26 . Another type of nanostructure that was studied is isolated nanoparticles 7,8,10,17,20,22,25 for which also an enhancement of low-and high-energy phonon modes as well as a broadening of the PDOS features was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The phonon density of states (PDOS) of low dimensional systems is expected to be modified due to the restriction of phonon propagation [7][8][9][10][11] . Previously, clear differences between the phonon density of states of bulk and that of nanostructures have been observed, with as most commonly observed anomalies in the phonon spectra of nanostructures: an enhancement of low-energy modes, appearance of high-energy modes above the cut-off energy of the bulk material and a broadening of the PDOS features [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . For thin films, the broadening of features in the PDOS was attributed to phonon damping 13,19,27,28 and the enhancement of low-energy phonon modes due to the appearance of surface modes 14,19,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrational properties of nanoscrystalline materials (nanocomposites) have been studied extensively experimentally by inelastic neutron scattering and nuclear resonant inelastic X-ray scattering (NRIXS) 9,[32][33][34][35][36][37][38][39][40][41][42] , as well as theoretically 7,8,10,13,[43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%